Image analysis on disintegrated concrete at the post-heating stage - Akca, A. H.; Özyurt, N. (Revista ALCONPAT, 2020)
The relation between crack growth and reduction in the compressive strength after high temperature exposure and after air re-curing was investigated in this study. Concrete specimens were heated to 1000 ºC and they were subjected to air re-curing for 28 days. During re-curing period, their heated surfaces were monitored by using a digital single-lens reflex camera and the images were analyzed by using image analysis software. After cooling, the maximum reduction in the compressive strength of concrete was 49.5% and that of air re-cured concrete was 66.8%. Image analyses showed high correlations between crack growth and reduction in the compressive strength. This non-destructive method has the potential to represent the extent of damage in concrete after high temperature exposure.